Health Shocks, Social Insurance, and Firms - Aniko Biro; István Boza; Attila Gyetvai; Daniel Prinz (Institute of Labor Economics (IZA), 2024)
We study the role that firms play in social insurance benefit uptake after their workers experience health shocks. Social insurance in our setting, Hungary, is universal and comprehensive, thus allowing us to quantify the heterogeneous impact of firms on benefit uptake and labor market outcomes on top of the social safety net. Using matched employer-employee administrative data linked to individual-level health records, we find that firm responses to worker health shocks are heterogeneous. Workers hit by a health shock at high-quality firms are less likely to take up disability insurance or exit the labor force than those at low-quality firms. These empirical patterns are consistent with worker-firm match quality increasing in firm quality in a setting where recovery from health shocks is uncertain. Our results imply that beyond higher wages, high-quality firms also offer more protection against the consequences of health shocks. This suggests that heterogeneous firm behavior should be taken into account when designing social insurance policies.
Keywords: H55; I10; J22; J23; 330; health shock; disability insurance; firm heterogeneity